Strengthening Biosecurity in Iraq: Development of a National Biorisk Management System - Al Jewari, Mahdi F. H.; Koblentz, Gregory D. (Frontiers in Public Health, 2016)
Since 2004, the Republic of Iraq has undertaken a concerted effort to comply with all of its international obligations to prevent the proliferation of chemical, biological, radiological, and nuclear (CBRN) weapons. A centerpiece of this effort is Iraq’s development of a national biorisk management system to prevent, prepare for, and respond to naturally occurring and deliberate biological threats. The Iraqi National Monitoring Authority (INMA), which is responsible for CBRN security and nonproliferation in Iraq, has played a key role in establishing this system. This article provides an overview of Iraq’s international nonproliferation commitments, describes the legal and organizational steps it has taken to implement these commitments, and examines current initiatives to strengthen Iraq’s biosecurity.